Analisis Average Length Of Stay Pasien Typhoid Fever di RSUD Harapan Doa Kota Bengkulu - Heltiani, Nofri; Desmiany Duri, Iin; Ramadani, Niska (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2021)
Average Length Of Stay (LOS) is an important indicator in determining the success of therapy for a disease and is also related to the cost of care incurred by the patient. the ideal value of AvLOS is 6-9 days. The level of AvLOS is influenced by the complications experienced by the patient. Typhoid fever is an endemic disease in Indonesia that knows no age and gender boundaries, and can cause various complications in the form of bleeding and intestinal perforation which can often lead to death. Based on the initial survey, the visit of typhoid fever patients in the last three years at Harapan Doa Hospital, Bengkulu City has increased, namely 2017 (11.02%), 2018 (13.47%) and 2019 (17.935) of the total visits/year, however, in 2020 it decreased (15.08%) due to the Covid-19 pandemic. This affects the AvLOS value and the cost received by the hospital. The purpose of this study was to determine the AvLOS value of typhoid fever patients at Harapan Doa Hospital, Bengkulu City. The type of research used is descriptive with a cross sectional approach. The sample of this study used a total population of 121 patients who were analyzed univariately using the AvLOS formula. The results of the univariate analysis, from the calculation results obtained that the total length of stay (LD) of typhoid fever patients was 395 days/year with AvLOS 3.18 days/year, the number of typhoid fever patients was out of life 124 (100%) patients, AvLOS of typhoid fever patients based on age group. The highest was found in the age group >1-5 years, namely 5.17 days compared to the age group >44-65 years, namely 3.43 days and >65 years, namely 3 days, where typhoid fever was accompanied by complications/companies. AvLOS of typhoid fever patients based on gender was found in female sex at 3.31 days with a total of 59 patients compared to male sex at 3.23 days with a total of 5 people. It is hoped that the hospital will formulate a clinical pathway for Typhoid Fever Treatment so that the quality of service for typhoid fever cases is in the efficientcategory.